Design and optimization of a wideband impact mode piezoelectric power generator - Basari, Amat Amir; Seiji, Hashimoto; Bunji, Homma; Hiroaki, Okada; Hideki, Okuno; Shunji , Kumagai (2016)
This paper proposes a new design of an impact mode piezoelectric power generator that is able to operate in a wide frequency bandwidth by using a round piezoelectric ceramic as the energy converter. The evaluation results show that the output of the power generator can be optimized by implementing a so-called indirect impact configuration. To realize this type of configuration, a shim plate is placed between the piezoelectric ceramic and the hitting structure. At a certain base excitation frequency, the output efficiency of this configuration increases to about 4.3 times that of the direct impact configuration. Furthermore, it is demonstrated that the designated power generator is able to generate electric energy up to approximately 1.57 mJ within 120 s from the vibration of a moving vehicle.